1988
DOI: 10.1016/s0140-1971(88)80032-0
|View full text |Cite
|
Sign up to set email alerts
|

A review of the literature on family therapy with adolescents 1979–1987

Abstract: SummarySince the initial publication of our article, significant developments have occurred in the literature pertaining to the application of family therapy to problems of adolescents. A primary change has been quantitative. As is evident from the problem listing above, a great number of articles have been written addressing a continually expanding array of presenting complaints.Similarly, the recent review clearly indicated that a full range of family therapy models has been represented in the literature sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…When describing sample inclusion criteria, 10 reviews (Alexander et al, 2002; Austin et al, 2005; Breunlin, Breunlin, Kearns, & Russell, 1988; Cottrell & Boston, 2002; Dumas, 1989; Gordon, 1995; Henggeler & Sheidow, 2003; Huey & Henggeler, 2001; Sexton, 2009; Waldron & Turner, 2008) refer to study participants, but the criteria are not elucidated well and include phrases such as “light to severe offenses,” “habitually truant,” “soft” juvenile offenders, and “serious juvenile offenders.” There is no definition of these terms and no explanation of what level of behavior is present. There is a great deal of room for interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When describing sample inclusion criteria, 10 reviews (Alexander et al, 2002; Austin et al, 2005; Breunlin, Breunlin, Kearns, & Russell, 1988; Cottrell & Boston, 2002; Dumas, 1989; Gordon, 1995; Henggeler & Sheidow, 2003; Huey & Henggeler, 2001; Sexton, 2009; Waldron & Turner, 2008) refer to study participants, but the criteria are not elucidated well and include phrases such as “light to severe offenses,” “habitually truant,” “soft” juvenile offenders, and “serious juvenile offenders.” There is no definition of these terms and no explanation of what level of behavior is present. There is a great deal of room for interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…There is a great deal of room for interpretation. Waldron and Turner (2008) report outcomes for youth diagnosed with “heavy alcohol abuse”; Dumas (1989) reports the participants were court referred; Austin, Macgowan, and Wagner (2005) discuss a sample that required a substance abuse diagnosis; and Breunlin, Breunlin, Kearns, and Russell (1988) report on a study with status offenders. These are definable categories which are far more objective and useful when examining the quality of design and methodology in the included reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Listening to the client’s voice is increasingly being recognized as essential to developing successful therapeutic treatments (Barnard & Kuehl, 1995). This is problematic for parents of adolescents who have had few chances to voice their perceptions about the experience of family therapy (Breunlin, Breunlin, Kearns, & Russell, 1988; Kuehl, Newfield, & Joanning, 1990; Mann & Bordin, 1991). While some studies indicate that early termination of therapy is often the result of poor parent‐therapist relationship, it has also been found that parents of adolescents in therapy are supportive, respectful, and helpful partners in the therapeutic process (Kuehl et al., 1990; Nevas & Farber, 2001).…”
Section: Theoretical Frameworkmentioning
confidence: 99%